Integration of Life Skills in Pétanque Training Programs within the Positive Youth Development Framework (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Integrating life skills into sport programs, including pétanque, is an effective way to promote Positive Youth Development (PYD). This approach enhances youth quality, protects them from negative environmental influences, and strengthens their roles as agents of change. This study aimed to compare the effects of pétanque training with life-skill integration and training without life-skill integration on improving PYD. An experimental study with a pretest-posttest control group design was employed, involving 24 students who were members of the Siliwangi University pétanque student activity unit selected through purposive sampling. The samples were divided into two groups, including experimental (n=12) and control (n=12) groups. Measurements were conducted using the Life Skills Scale for Sport (LSSS). The findings showed that pétanque training integrated with life skills significantly improved PYD, whereas training without this integration did not have a significant effect. These results can serve as a consideration for young pétanque coaches in designing training programs that focus not only on technical aspects but also support the character development and psychosocial maturity of the participants.